High performance tunnel field effect transistors based on in-plane transition metal dichalcogenide heterojunctions. (1st November 2018) - Choukroun, Jean; Pala, Marco; Fang, Shiang; Kaxiras, Efthimios; Dollfus, Philippe
Abstract: In-plane heterojunction tunnel field effect transistors based on monolayer transition metal dichalcogenides are studied by means of self-consistent non-equilibrium Green's functions simulations and an atomistic tight-binding Hamiltonian. We start by comparing several heterojunctions before focusing on the most promising ones, i.e. WTe2 -MoS2 and MoTe2 -MoS2 . The scalability of those devices as a function of channel length is studied, and the influence of backgate voltages on device performance is analyzed. Our results indicate that, by fine-tuning the design parameters, those devices can yield extremely low subthreshold swings (<5 mV/decade) and I ON / I OFF ratios higher than 10 8 at a supply voltage of 0.3 V, making them ideal for ultra-low power consumption.